Emergence and Characterization of Acute Coronary Syndrome in Adults After Confirmed or Missed History of Kawasaki Disease in Japan: A Japanese Nationwide Survey - Mitani, Yoshihide; Tsuda, Etsuko; Kato, Hitoshi; Higaki, Takashi; Fujiwara, Masako; Ogawa, Shunichi; Satoh, Fumiko; Nakamura, Yoshikazu; Takahashi, Kei; Ayusawa, Mamoru; Kobayashi, Tohru; Ichida, Fukiko; et al. (Frontiers in Pediatrics, 2019)
Abstract Background: Acute coronary syndrome (ACS) which is emerging in adults long after confirmed (followed-up or lost-to-follow) or missed Kawasaki disease (KD) is poorly characterized. Methods and Results: A Japanese retrospective nationwide hospital-based questionnaire survey of ACS during 2000-09 was conducted to characterize such patients. Among a total of 67 patients (median age 35 yo, male 76%) recruited, low conventional coronary risks ( 1/6) was noted in 75%, a diagnosis of ST-elevation and myocardial infarction or cardiac arrest in 66%, medication before ACS in 22% (warfarin in 4%), and no prior history of acute myocardial infarction in 94%. One-month mortality was 19%. KD diagnosis was made in 32 during acute illness (Group A), in which 17 were lost to follow, and retrospectively in the other 35 from coronary imaging at ACS (Group B). Group A developed ACS at lower coronary risks (2/5 in 87% vs 65% in group B, p=.043) at younger age (26.5 yo vs. 40 yo, p<.001). In group A, followed-up patients developed ACS under medication before ACS (87% vs. 0% in lost-to-follow patients, p<.001) for giant aneurysm in culprit lesions (69% vs. 29%, p=.030). One-month mortality was comparable between groups A and B, and between patients followed-up and lost-to-follow in group A. The culprit lesion in group A was characterized by the association of an aneurysm 6 mm in acute KD (100%), lack of significant stenosis (61%) or giant aneurysm (50%) in the long-term (median interval 16y), and the presence of intravascular ultrasound-derived calcification at ACS (86%). Conclusions: The present retrospective nationwide questionnaire survey demonstrated nationwide emergence of initial ACS in young adults at low coronary risks, who are followed-up or lost-to-follow after confirmed KD and initial coronary aneurysms 6 mm.